1992
DOI: 10.1152/ajpcell.1992.262.3.c731
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and propagated calcium release in isolated cardiac myocytes viewed by confocal microscopy

Abstract: Laser scanning confocal microscopy of the Ca(2+)-sensitive fluorophore fluo-3 has been used to investigate spontaneous and propagated calcium release at high temporal and spatial resolution in enzymatically dispersed rat cardiomyocytes. Waves of fluorescence which propagated throughout the cytosol were evident in spontaneously contracting cardiac cells containing fluo-3, but not in cells containing Ca(2+)-insensitive fluorophores [2',7'-bis (carboxyethyl)-5,6-carboxyfluorescein, SNARF-1, rhodamine-123, or tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
41
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 24 publications
4
41
1
Order By: Relevance
“…We have found that store depletion (CPA, thapsigargin), PLC inhibition (U73122) as well as blockade of IP 3 Rs abolished spontaneous Ca 2+ transients, indicating that the transients are due to release from cytoplasmic stores rather than Ca 2+ entry from extracellular space. Spontaneous cytosolic Ca 2+ elevations arising from the ER were previously described in many excitable and non-excitable isolated cell types, including neutrophils [31], myocytes [32,33], interstitial cells [34], astrocytes [35] and neurons [36]. However, in many of these cell preparations, spontaneous cytosolic calcium elevations occur at much higher frequencies, being rather oscillatory than stochastically distributed.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that store depletion (CPA, thapsigargin), PLC inhibition (U73122) as well as blockade of IP 3 Rs abolished spontaneous Ca 2+ transients, indicating that the transients are due to release from cytoplasmic stores rather than Ca 2+ entry from extracellular space. Spontaneous cytosolic Ca 2+ elevations arising from the ER were previously described in many excitable and non-excitable isolated cell types, including neutrophils [31], myocytes [32,33], interstitial cells [34], astrocytes [35] and neurons [36]. However, in many of these cell preparations, spontaneous cytosolic calcium elevations occur at much higher frequencies, being rather oscillatory than stochastically distributed.…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2ϩ waves in the perfused hearts exhibited intracellular propagation similar to those in isolated myocytes studied previously. [7][8][9][10][11][12][13] Sequential X-Y images at 2 mmol/L [Ca 2ϩ ] o showed that the waves propagated along the longitudinal axis of the cells ( Figure 1C). The corresponding line-scan images ( Figure 1D) revealed that the waves proceeded at a constant velocity of Ϸ90 m/s in 1 (a) or 2 (b) directions.…”
Section: Methodsmentioning
confidence: 99%
“…4 -6 has been called the Ca 2ϩ wave 7,8 and is regarded as the origin of oscillatory membrane potentials leading to triggered arrhythmias. 9 For the past decade, the properties of Ca 2ϩ waves in cardiac myocytes have been studied precisely after the advent of fluorescent Ca 2ϩ indicators [7][8][9][10][11][12][13] and laser scanning confocal microscopy. [11][12][13] Despite ample information on Ca 2ϩ waves, 7-13 the role of the waves in the heart in situ is poorly understood.…”
mentioning
confidence: 99%
“…When the SR is heavily loaded or overloaded with Ca , the SR appears to release Ca 2ϩ regeneratively [5]. Under this condition, Ca 2ϩ released from the SR diffuses over the adjacent SR to trigger a large amount of Ca 2ϩ release, resulting in a propagating Ca 2ϩ wave [6][7][8][9]. Since the Ca 2ϩ wave and the resulting contraction wave occur under some pathological conditions [10][11][12][13], it is quite important to study the two types of Ca 2ϩ release from the SR to give information about clinical heart dysfunction.…”
mentioning
confidence: 99%
“…In regard to the duration of the [Ca 2ϩ ] transient in the Ca 2ϩ wave, it is a matter of controversy whether the SR Ca 2ϩ release takes a similar duration in both the Ca 2ϩ wave and the physiological twitch. Early reports suggested that [Ca 2ϩ ] transients or twitches at a sarcomere level had a longer duration in the Ca 2ϩ wave than the action potentialtriggered twitch [7][8][9]. On the contrary, Cheng et al [14], using a laser scanning confocal microscope, reported that the [Ca 2ϩ ] i transient of the Ca 2ϩ wave had ] i transient is slower in the Ca 2ϩ wave than in the action potentialtriggered twitch.…”
mentioning
confidence: 99%